Updated View on the Relation of the Pineal Gland to Autism Spectrum Disorders - Shomrat, Tal; Nesher, Nir (Frontiers in Endocrinology, 2019)
Identification of the biological features of autism is essential for designing an efficient treatment and for prevention of the disorder. Though the subject of extensive research, the neurophysiological features of autism remain unclear. One of the proposed biological causes of autism is malfunction of the pineal gland and deficiency of its principal hormone, melatonin. The main function of melatonin is to link and synchronize the body's homeostasis processes to the circadian and seasonal rhythms, and to regulate the sleep-wake cycle. Therefore, pineal dysfunction has been implicated based on the common observation of low melatonin levels and sleep disorders associated with autism. In this perspective, we highlight several recent findings that support the hypothesis of pineal gland/melatonin involvement in autism. Another common symptom of autism is abnormal neuroplasticity, such as cortical overgrowth and dendritic spine dysgenesis. Here, we synthesize recent information and speculate on the possibility that this abnormal neuroplasticity is caused by hyperactivity of endogenous N,N-dimethyltryptamine (DMT). The pineal gland was proposed as the source of DMT in the brain and therefore, our assumption is that besides melatonin deficiency, pineal dysfunction might also play a part in the development of autism through abnormal metabolism of DMT. We hope that this manuscript will encourage future research of the DMT hypothesis and reexamination of several observations that were previously attributed to other factors, to see if they could be related to pineal gland/melatonin malfunction. Such research could contribute to the development of autism treatment by exogenous melatonin and monitored light exposure.